2016
DOI: 10.1111/age.12420
|View full text |Cite
|
Sign up to set email alerts
|

Use of single nucleotide polymorphisms in candidate genes associated with daughter pregnancy rate for prediction of genetic merit for reproduction in Holstein cows

Abstract: We evaluated 69 SNPs in genes previously related to fertility and production traits for their relationship to daughter pregnancy rate (DPR), cow conception rate (CCR) and heifer conception rate (HCR) in a separate population of Holstein cows grouped according to their predicted transmitting ability (PTA) [≤-1 (n = 1287) and ≥1.5 (n = 1036)] for DPR. Genotyping was performed using Sequenom MassARRAY(®) . There were a total of 39 SNPs associated with the three fertility traits. The SNPs that explained the greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 45 publications
3
72
1
10
Order By: Relevance
“…Brøndum et al [2] added 1623 sequence variants selected by GWA from multiple breeds to a custom chip and reported gains in reliability that averaged about 2 percentage points. Small improvements (0.2 percentage points) from adding SNPs that are located in genes associated with fertility were observed by Ortega et al [9], which is consistent with gains reported in this and earlier studies [12]. Using selected sequence variants and giving extra weight to candidate variants or QTL can improve predictions across breeds [5, 2427], but advantages of focusing on candidate variants decrease if not all QTL are in the variant set [6].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Brøndum et al [2] added 1623 sequence variants selected by GWA from multiple breeds to a custom chip and reported gains in reliability that averaged about 2 percentage points. Small improvements (0.2 percentage points) from adding SNPs that are located in genes associated with fertility were observed by Ortega et al [9], which is consistent with gains reported in this and earlier studies [12]. Using selected sequence variants and giving extra weight to candidate variants or QTL can improve predictions across breeds [5, 2427], but advantages of focusing on candidate variants decrease if not all QTL are in the variant set [6].…”
Section: Discussionmentioning
confidence: 96%
“…Nearly 40 million variants have been identified from whole-genome sequence (WGS) data for over 1500 bulls, and several strategies to impute these variants to additional animals and use them in genetic evaluation for economic traits show potential [18]. For example, candidate variants can be targeted to specific traits such as genes related to fertility, thereby slightly improving reliability for daughter pregnancy rate by 0.2 percentage points when 39 single nucleotide polymorphisms (SNPs) were added to the marker set used for genomic prediction [9]. The number of sequenced animals should continue to increase as researchers examine more families and the costs of generating data continue to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…COQ9, along with other COQ proteins (COQ2-COQ8), is involved in the biosynthesis of COQ10 (Tran and Clarke, 2007;Ben-Meir et al, 2015), which is a component of the mitochondrial electron transport system that is required for mitochondrial adenosine triphosphate synthesis. The A allele, which has a frequency of 49 to 51% in Holsteins (Ortega et al, 2016a), is associated with enhanced mitochondrial function (Ortega et al, 2017c). One possibility is that actions of hCG on reproductive tissues such as the endometrium (Shemesh et al, 2001) and corpus luteum (Niswender et al, 2000) have negative consequences when mitochondrial function is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…One SNP is an G → A missense mutation in coenzyme Q9 (COQ9) that causes an amino acid change from aspartic acid to asparagine at position 53 of the protein. The A allele is associated with higher genetic merit for daughter pregnancy rate (DPR) and cow conception rate (Cochran et al, 2013b;Ortega et al, 2016a) and higher phenotypic measurements of fertility (Ortega et al, 2017c). The A allele is also associated with more efficient mitochondria in peripheral blood mononuclear cells, and increased mitochondrial DNA copy number in oocytes (Ortega et al, 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…This gene expression was abundant in fish eggs after photo-stimulation treatment to induce ovulation (Bonnet, Fostier, & Bobe, 2007). Ortega, Denicol, Cole, Null, and Hansen (2016) in a GWAS identify a significant SNP associated with heifer conception rate inside the gene HSD17B7 in Holstein cows. This gene, located on BTA3 in bovine, is associated with production of estradiol, an important female hormone, in corpus luteum and with embryo development in mice (Gibori et al, 2009) and was involved in both sex steroid hormones synthesis, in human (Osuch et al, 2012).…”
Section: Genes and Qtls In The Validated Regionsmentioning
confidence: 99%